Complex representations of finite general linear groups - Küçük, Ebru Beyza. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In this thesis, we determine complex irreducible representations of GL(2,K), the group of 2 by 2 invertible matrices over a ﬁnite ﬁeld K. Actually, this is done by Ilya Piatetski-Shapiro in 1983. In his article [1], Shapiro classiﬁes the irreducible representations of the group GL(2,K) by using the deﬁnition of induced module de pends as a space of functions. The aim of this thesis is to rewrite the article using the induction module deﬁnition constructed by a tensor product. We start the thesis by reminding some basic deﬁnitions and theorems related to our topic. Then we de termine the commutator subgroup of GL(2,K) and introduce some special subgroups of GL(2,K). The number of irreducible representations of a ﬁnite group is equal to the number of conjugacy classes of that group. Hence we calculate the conjugacy classes of GL(2,K). We determine irreducible representations of GL(2,K) through irreducible representations of the subgroups of it and quotient groups.
Keywords: Finite fields (Algebra)